Road Traffic RFID Pedestrians Detecting System for Vehicles - Balog, Michal; Iakovets, Angelina; Hrehova, Stella (EAI Endorsed Transactions on Smart Cities, 2019)
Safe road traffic, clean environment, environmentally friendly vehicles and eco-buildings are components of the world’s vision of immediate future supported by scientists and statesmen. Aspiration for healthy environment and sustainable development of technologies give life for idea of smart cities which consist of all these visions towards modern world. The aim of research was connection pedestrians and alarm system of the vehicle to prevent road incidents with the help of RFID technology. There were proposed vehicle RFID system and tags for pedestrians. System was designed on the basis of scientists’ research in this area. The main factors influencing the construction of proposed system were working range of the system and coverage width of the reading devices. Further were compared existent subsidiary systems for drivers versus designed system. The study represents the expected effectiveness of the proposed RFID system as well as the ability to implement it even in old vehicle control systems.
Keywords: RFID; smart city; vehicles; detecting systems; accidents; pedestrians; road traffic